2004
DOI: 10.1096/fj.04-1978com
|View full text |Cite
|
Sign up to set email alerts
|

The neurovascular mechanism of clitoral erection: nitric oxide and cGMP‐stimulated activation of BKCachannels

Abstract: Female sexual function is under-studied, and mechanisms of clitoral engorgement-relaxation are incompletely understood. Penile erection results from nitric oxide (NO) -induced cyclic guanosine monophosphate (cGMP) accumulation. cGMP-dependent protein kinase (PKG) activates large-conductance, calcium-activated potassium channels (BK(Ca)), thereby hyperpolarizing and relaxing vascular and trabecular smooth muscle cells, allowing engorgement. We hypothesize rat clitorises relax by a similar mechanism. Rat clitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 56 publications
0
56
1
Order By: Relevance
“…These reports are consistent with the present findings of the contribution of KCa to PDE5 inhibitor-induced vasodilatation of HPRA. The lack of influence of KCa blockade on relaxations driven by PDE5 inhibition in HCC is, however, in contradiction to the previously reported sensitivity of sildenafil-induced relaxation to IbTx in HCC (Kun et al, 2009), and the suggested participation of KCa in PDE5 inhibitor-induced relaxation in rabbit clitoris (Gragasin et al, 2004) and mouse corpus cavernosum (Werner et al, 2008). Our results nevertheless were strengthened by the absence of significant effects of NS-8 or NS1619 on sildenafil-induced relaxation of HCC.…”
Section: Figurecontrasting
confidence: 99%
See 1 more Smart Citation
“…These reports are consistent with the present findings of the contribution of KCa to PDE5 inhibitor-induced vasodilatation of HPRA. The lack of influence of KCa blockade on relaxations driven by PDE5 inhibition in HCC is, however, in contradiction to the previously reported sensitivity of sildenafil-induced relaxation to IbTx in HCC (Kun et al, 2009), and the suggested participation of KCa in PDE5 inhibitor-induced relaxation in rabbit clitoris (Gragasin et al, 2004) and mouse corpus cavernosum (Werner et al, 2008). Our results nevertheless were strengthened by the absence of significant effects of NS-8 or NS1619 on sildenafil-induced relaxation of HCC.…”
Section: Figurecontrasting
confidence: 99%
“…Previous studies carried out in different tissues, including erectile tissues, have described intracellular activation of KCa by cGMP generated in smooth muscle, contributing to NO/cGMP-mediated relaxation (Sausbier et al, 2000;Lee and Kang, 2001;Gragasin et al, 2004;Tanaka et al, 2004). It has been proposed that the cGMP-induced activation of BK channels is mediated by cGMP-dependent kinase (Schubert and Nelson, 2001;Zhou et al, 2001).…”
Section: Figurementioning
confidence: 99%
“…Female sexual function showed a combination of endocrine, vascular and neuromuscular factors that regulate important steps of female sexual reaction as increased genital blood flow, enlarged clitoral diameter and length, increased vaginal luminal diameter and lubrication, wall engorgement [59,60]. …”
Section: Discussionmentioning
confidence: 99%
“…Pelvic vascular injury and neuropathy induced by some metabolic factors as dyslipidemia, glucose intolerance, insulin resistance, diabetes mellitus, and systemic arterial hypertension could cause clitoral insufficiency and reduced vaginal engorgement resulting in vasculogenic FSD [37,59,60,61,62,63]. In particular obesity, as the result of excessive accumulation of body fat, is strongly associated with MS.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the arterial blood supply supplying the female pelvic anatomy relating to the presence of atherosclerosis of the arterial bed can lead to decreased vaginal engorgement and clitoral insufficiency syndrome resulting in vasculogenic FSD (Doumas et al, 2005, Gragasin et al, 2004. Additionally the prevalence of Metabolic Syndrome increases during the fifth and sixth decades of women's lives and also coincides with the onset of the menopause hence associated with the lower oestrogenic milieu which enhances risk factors for metabolic syndrome such as increased insulin resistance, obesity and hyperglycaemia (Otunctemur et al, 2014).…”
Section: Diabetesmentioning
confidence: 99%